STUDENTS’ PERCEPTION OF USING QUIZIZZ APPLICATION IN READING CLASS - Lina Iswanda; Jenny Elvinna Manurung; Heru Setiawan (Program Pendidikan Bahasa Inggris Universitas Tridinanti, 2025)
Integrating technology into the classroom is essential for enhancing student engagement and learning outcomes. Quizizz is widely adopted to promote interactive and student-centered instruction. This study investigates students’ perceptions and the perceived benefits of using the Quizizz application in reading lessons at SMA Negeri 11 Palembang during the 2024/2025 academic year. A quantitative approach was used, involving 132 tenth-grade students selected through purposive sampling. Data were collected via a closed-ended questionnaire based on five aspects: Perceived Usefulness (PU), Perceived Ease of Use (PEOU), Attitude (A), Skill Engagement (SKE), and Interaction Engagement (IE), using a Likert scale. The findings indicate that students generally have positive perceptions of Quizizz. They appreciate its interactive interface, multimedia features, instant feedback, and gamification elements like leaderboards, which enhance motivation and engagement. Students reported that Quizizz made reading activities more enjoyable, accessible, and dynamic, contributing to improved participation and focus. Quantitative data show that 55.74% and 56.90% of students chose